Identification of hub genes associated with decreased fertility in male mice of advanced paternal age - Gao, Yang; Zhang, Ting; Wang, Yan; Lv, Haitao; Yan, Xiangming; Fu, Longlong; Liu, Ying (Frontiers in Cell and Developmental Biology, 2025)
IntroductionAging and delayed parenthood are major social concerns. Men older than 35 years, which is an advanced paternal age, experience reduced sperm quality and fertility.MethodsIn this study, 12-month-old mice served as a model for males of advanced paternal age. RNA sequencing (RNA-seq) of epididymides from 2- and 12-month-old mice was performed.ResultsSpermatogonia and sperm counts were significantly lower in these mice. We identified 449 differentially expressed genes by RNA-seq. Altered pathways were enriched using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Moreover, nine hub genes were identified from the DEGs, along with DEGs associated with mitochondria.DiscussionThese results could enhance understanding of the molecular mechanisms underlying decreased male fertility in men of advanced paternal age and may aid in developing targeted treatment for male infertility related to aging.